Distribution, Morphometrics and DNA barcoding of Archotermopsis wroughtoni Desneux (Termopsidae: Blattodea) in District Mansehra, Pakistan - Hamid Ur Rahman; Sobia Attaullah; Tariq Mahmood; Ashfaq Ahmad (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2023)
Archotermopsis wroughtoni is a primitive termite species with distinct biological and behavioral features. Despite its presence in temperate regions worldwide, including the Oriental region, there is a lack of data on the current distribution of this species in the Mansehra district of Pakistan. Samples were collected from forested areas, including the Kaghan, Naran, Mahandri, and Shogran valleys. The distribution of A. wroughtoni was determined by observing decayed and fallen wooden logs, and host plants were identified to assess the species’ host preference. Morphometric identification was performed following relevant literature, and the barcoding technique of mtDNA COII was used to authenticate the species. Phylogenetic analyses were conducted using the neighbor-joining and maximum parsimony methods. The study revealed the presence of A. wroughtoni in the forests of northern Mansehra, where it preferred tree species such as Cedrus deodara and Pinus excelsa for nest construction and foraging. The findings of this research will contribute to future studies on the biology and ecology of A. wroughtoni and aid in developing conservation strategies for this species and other social insects.